Asuhan Keperawatan Pada Ibu Postpartum Dengan Gangguan Pola Tidur Dan Penerapan Refleksologi Kaki Untuk Meningkatkan Kualitas Tidur - Rifda Hasanah Fauzi (2023)
Sleep is a basic human need to restore energy and maintain metabolic balance. The quality of sleep for postpartum mothers is important because the quality of sleep is a person's satisfaction from sleep so that when they wake up their bodies feel fresher. However, postpartum mothers often experience sleep quality problems during the postpartum period. One of the non-pharmacological therapies that can help improve sleep quality is foot reflexology. Foot reflexology, namely massage in the area of the foot that is connected to other parts of the body through the nervous system. The purpose of this study was to analyze nursing care with the application of foot reflexology in postpartum mothers. Respondents involved were 2 people including managed patients and resume patients who were given foot reflexology interventions. This intervention was carried out for seven days with a frequency of once per day for 15 minutes. The instrument used as a measure of sleep quality for postpartum mothers is the Postpartum Sleep Quality Scale (PSQS). The results of this study the problem of sleep pattern disturbances can be resolved after foot reflexology therapy which is marked by statements of sleep satisfaction and the body becomes relaxed.